An Atypical Giant Right Atrial Myxoma Presented with Minimal Symptoms - Huseyın Goksuluk; Orhan Veli Doğan; Barbaros Dokumacı; Ilker Ozer (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2016)
Introduction Primary tumours of the heart are not common and the prevalence of cardiac tumors ranges from 0,001% to 0,3% at autopsy [1]. Over 70% of primary cardiac tumors are benign and the most common form of these primary tumours are myxomas. Most of the myxomas are located in the left atrium (%75-80), arising from the interatrial septum at the border of the fossa ovalis [2]. Larger tumors are more likely to be associated with cardiovascular symptoms [3]. Commonly observed symptoms and signs are dyspnea, pulmonary edema, cough, peripheral edema and fatigue. Constitutional symptoms (fever, weight loss) are seen in around 30% of patients. Laboratory abnormalities (anemia and elevations in the erythrocyte sedimentation rate, C-reactive protein) are present in 35 % of patients [4]. This case report show us discrepancy between giant right atrial myxoma and atypical symptom of patient. Once a cardiac myxoma is diagnosed, surgical excision should be performed without delays because of the risk of thromboembolic events [5-7], syncope and sudden cardiac death. Generally, surgical treatment is definitive and recurrence is uncommon.